(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
This study examines the role of Artificial Intelligence (AI) in enhancing operational efficiency in logistics and supply chain management (SCM). It highlights how AI automates processes, improves demand forecasting, optimises inventory management, and enhances route planning. The research also explores AI’s impact on predictive maintenance and customer experience through real-time tracking and chatbots. By leveraging advanced algorithms, organisations can achieve greater accuracy, reduce costs, and increase flexibility, gaining a competitive advantage in the market. The findings provide valuable insights for practitioners and researchers on the strategic opportunities presented by AI in logistics and SCM.